The study of instability of mechanical equilibrium in three-component gas mixture containing propane by the method of Stefan-Maxwell - Молдабекова, М.С.; Әсембаева, М.К.; Мукамеденқызы, В.; Абдулаева, Ә.Б. (Recent Contributions to Physics, 2016)
The article presents a comparison of the experimental data studies of the instability of mechanical equilibrium in isothermal three-component gas mixtures in the diffusive mixing is calculated with the method of the Stefan-Maxwell.Experimental data for systems containing propane, nitrous oxide and carbon dioxide were obtained in two bulb method.In experiments it was found that for predefinemessage propane depending on pressure and initial concentrations of propane in a diffusion device the maximum transfer is observed at aрmax certain pressure value. The measurements showed that the pressure value рmax different for a binary mixture in a three-component system with different initial (starting) concentration of the components. Nature calculated based on the concentration of propane in predefinemessage bottom flask from its initial concentration and pressure is qualitatively consistent with experimental data. Theoretical study has shown that as experience increases the initial concentration of propane in the binary mixture propane – nitrous oxide leads to a decrease, and then increase the pressure at which there is maximum transfer of propane was investigated for a particular system. This shift component is not characteristic of molecular diffusion.